Simulating Radio Variability Using Tracers of the Interstellar Medium - Charlton, Elliott George (Curtin University, 2021)
This thesis examines the simulation and modelling of interstellar scintillation at low radio frequencies. We improve upon an existing scattering model which allows us to predict the magnitude of variability due to interstellar scintillation. We then test this model using a simulation of radio sources compared against eight radio surveys. We find that fewer than 0.1% of radio sources exhibit refractive interstellar scintillation at 185 mega-hertz.